Mozaika w Casa de los Pájaros w Italice (Santiponce, Sevilla) jako wyraz rzymskiej fascynacji ptakami - Głowa, Anna; Zimnowodzka, Anna (Collectanea Philologica, 2024)
The aim of this article is to analyze and interpret a mosaic in one of the Roman houses (the House of Birds) in Italica (today Santiponce, Sevilla). This mosaic, depicting 33 birds of various species in square fields, will be considered in the context of the scientific interest in birds, which dates back to the Hellenistic era, as well as the custom of arranging aviaries in the country villas.